Penerapan “One Person One Example” dalam Pembelajaran Ilmu Tajwid sebagai Upaya Menumbuhkan Rasa Cinta Kepada Al-Qur’an - Tri Marfiyanto; Ria Yuliasti Ningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
The Qur'an is a collection of the words of Allah SWT which were revealed to the Messenger of Allah SAW through the angel Gabriel which was then taught to mankind. Reading the Qur'an is part of the proof of the faith of Muslims in maintaining and loving the words of Allah, because it is known that the Qur'an has such great and meaningful content in human life and the universe and its knowledge. This community service was carried out at the TPQ Musholla Al-Hikamh Batam which focused on providing an understanding to the TPQ students of the Al-Qur'an class on the science of tajwid, so that the students were allowed in their learning to provide an example of a tajwid reading